(3QhVI GdWQGFa aj QSe GdeUGMas - (3HQgGf GdOjf EHQGgje Hf CHj HcQ GdLYHQj,J (B687 (3g` s ((3eMeO Hf YHO GdcQje GdNdjd s)
(3ChdgG (B:s
(3Gddg CMeO YdGe GdZjhH Ydi BdGFg MeO QGMi GdYaI eHJgdkG s
(3bhHdJ HfSNI bhHdJ Ydi GdfGXes
(3hgj efXheIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B10 s
Keywords: (3GdbQGAGJ hGdJLhjOs